2016
DOI: 10.1364/ol.41.003273
|View full text |Cite
|
Sign up to set email alerts
|

Fractional nonparaxial accelerating Talbot effect

Abstract: We demonstrate the fractional Talbot effect of nonparaxial accelerating beams, theoretically and numerically. It is based on the interference of nonparaxial accelerating solutions of the Helmholtz equation in two dimensions. The effect originates from the interfering lobes of a superposition of the solutions that accelerate along concentric semicircular trajectories with different radii. Talbot images form along certain central angles, which are referred to as Talbot angles. The fractional nonparaxial Talbot e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 38 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Today, research efforts that involve the Talbot effect include atomic optics [4][5][6], quantum optics [7,8], nonlinear optics [9][10][11], waveguide arrays [12], photonic lattices [13], Bose-Einstein condensates [14,15], and electronics [16], to name a few. It is worth mentioning that the Talbot effect can also be observed by using spherical waves [17] and accelerating beams [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Today, research efforts that involve the Talbot effect include atomic optics [4][5][6], quantum optics [7,8], nonlinear optics [9][10][11], waveguide arrays [12], photonic lattices [13], Bose-Einstein condensates [14,15], and electronics [16], to name a few. It is worth mentioning that the Talbot effect can also be observed by using spherical waves [17] and accelerating beams [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the divided wavefront will be individually bent in each ENZ element with a different angle, thus constructively interfering in the focal region along the caustic curve. However, such caustic curve is now a regular polygon approaching an incomplete circle, which leads to a fractional Talbot effect [28]. Note that in the numerical simulations shown in Fig.…”
Section: Implementation Of Ultrathin Enz Metacoatingsmentioning
confidence: 92%
“…Without such an approximation, one investigates nonparaxial optical problems using the Helmholtz equation that follows directly from the Maxwell's equations [15]. It has been demonstrated that the solutions of two-dimensional (2D) Helmholtz equation are plane waves in Cartesian coordinates, Bessel beams in circular cylindrical coordinates [16][17][18][19], Mathieu beams in elliptic cylindrical coordinates [20,21], and Weber beams in parabolic cylindrical coordinates [20,[22][23][24][25]. In addition to the 2D case, one can also solve the 3D Helmholtz equation for the 3D accelerating beams utilizing the Whittaker integral [16,26,27].…”
Section: Introductionmentioning
confidence: 99%